Accuracy of digital templating in uncemented primary total hip arthroplasty: which factors are associated with accuracy of preoperative planning?. Issue 3 (May 2023) - Adamczyk, Andrew; Laboudie, Pierre; Nessek, Hamid; Kim, Paul R; Gofton, Wade T; Feibel, Robert; Grammatopoulos, George
Background: Preoperative planning is a fundamental step for successful total hip arthroplasty (THA). Studies have highlighted the accuracy of preoperative digital templating for estimating acetabular cup and stem size. Stem design such as single-wedge metadiaphyseal (Type 1 stem) versus mid-short stem (microplasty) and surgical approach (anterior, direct lateral or posterior) have not been well investigated as predictors of THA templating accuracy. Methods: 204 patients (220 hips) who had undergone elective THA between November 2016 and December 2019 and presented a saved preoperative template were retrospectively reviewed. Templates from 5 different surgeons were involved in the analysis. 3 different approaches were used: direct lateral (DL), posterior (PA), direct anterior (DAA). 2 different stem designs were used: single-wedge metadiaphyseal and single-wedge mid-short (Biomet Taperloc Microplasty), while the acetabular component remained the same. Bivariate and multivariate regression analyses were performed to determine predictors of accuracy. Results: Femoral component size templating accuracy was significantly improved when using the single-wedge mid-short stem (Taperloc Microplasty) design when performing bivariate analysis. Although accuracy of cup sizing was not affected by approach, precision was significantly better in the PA group ( p  < 0.05). Accuracy of templating was found to be independent of BMI and gender but dependent on presence of calibration marker and stem design ( p  < 0.05). Conclusions: When striving for improved templating accuracy, acetabular and femoral component accuracy were best achieved using a calibration marker and a metaphyseal short femoral stem design.